Salivary Gland Secretory Carcinoma: Clinicopathologic and Genetic Characteristics of 215 Cases and Proposal for a Grading System - Baněčková, Martina; Thompson, Lester D R; Hyrcza, Martin D; Vaněček, Tomáš; Agaimy, Abbas; Laco, Jan; Simpson, Roderick H W; Di Palma, Silvana; Stevens, Todd M; Brcic, Luka; Etebarian, Arghavan; Dimnik, Katarina; et al. (The American journal of surgical pathology, 2023)
Salivary gland secretory carcinoma (SC), previously mammary analog SC, is a low-grade malignancy characterized by well-defined morphology and an immunohistochemical and genetic profile identical to SC of the breast. Translocation t(12;15)(p13;q25) resulting in the ETV6 :: NTRK3 gene fusion is a characteristic feature of SC along with S100 protein and mammaglobin immunopositivity. The spectrum of genetic alterations for SC continues to evolve. The aim of this retrospective study was to collect data of salivary gland SCs and to correlate their histologic, immunohistochemical, and molecular genetic data with clinical behavior and long-term follow-up. In this large retrospective study, we aimed to establish a histologic grading scheme and scoring system. A total of 215 cases of salivary gland SCs diagnosed between 1994 and 2021 were obtained from the tumor registries of the authors. Eighty cases were originally diagnosed as something other than SC, most frequently acinic cell carcinoma. Lymph node metastases were identified in 17.1% (20/117 cases with available data), with distant metastasis in 5.1% (6/117). Disease recurrence was seen in 15% (n=17/113 cases with available data). The molecular genetic profile showed ETV6 :: NTRK3 gene fusion in 95.4%, including 1 case with a dual fusion of ETV6 :: NTRK3 and MYB :: SMR3B . Less frequent fusion transcripts included ETV6 :: RET (n=12) and VIM :: RET (n=1). A 3-tiered grading scheme using 6 pathologic parameters (prevailing architecture, pleomorphism, tumor necrosis, perineural invasion (PNI), lymphovascular invasion (LVI), and mitotic count and/or Ki-67 labeling index) was applied. Grade 1 histology was observed in 44.7% (n=96), grade 2 in 41.9% (n=90), and grade 3 in 13.5% (n=29) of cases. Compared with low-grade and intermediate-grade SC, high-grade tumors were associated with a solid architecture, more prominent hyalinization, infiltrative tumor borders, nuclear pleomorphism, presence of PNI and/or LVI, and Ki-67 proliferative index >30%. High-grade transformation, a subset of grade 2 or 3 tumors, seen in 8.8% (n=19), was defined as an abrupt transformation of conventional SC into high-grade morphology, sheet-like growth, and a tumor lacking distinctive features of SC. Both overall survival and disease-free survival (5 and 10 y) were negatively affected by tumor grade, stage, and TNM status (each P <0.0001). SC is a low-grade malignancy with predominantly solid-microcystic growth patterns, driven by a gene fusion, most commonly ETV6 :: NTRK3 . There is a low risk for local recurrence and a good overall long-term survival, with a low risk for distant metastasis but a higher risk for locoregional lymph node metastasis. The presence of tumor necrosis, hyalinization, PNI and/or LVI, and positive resection margins correlate with higher tumor grade, less favorable prognosis, and increased mortality. The statistical results allowed us to design a 3-tiered grading system for salivary SC.
Keywords: antigen Ki-67; Mammary Analogue Secretory Carcinoma; slinné žlázy; Salivary Gland Neoplasms; Salivary Glands; Neoplasm Recurrence, Local; fúzní onkogenní proteiny; lidé; nekróza; Oncogene Proteins, Fusion; sekreční karcinom mamárního typu; nádory slinných žláz; Necrosis; retrospektivní studie; nádorové biomarkery; lokální recidiva nádoru; Ki-67 Antigen; Biomarkers, Tumor; Retrospective Studies; Humans